Migração partidária: uma reflexão acerca da “dança das cadeiras” no parlamento brasileiro - Alves de Oliveira, Maria Clécia; de Aguiar Pontes, Ysmênia (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2023)
ABSTRACT: The scope of this research is the study of party loyalty, an Electoral Law institute introduced in the Brazilian legal system through Constitutional Amendment nº 1/1969, capable of conferring legitimacy to the party representative system, if applied effectively. Starting from the premise that the political party is an essential instrument for the realization of the democratic ideal raised by the Federal Constitution of 1988, we sought to analyze the effects of the exchange of legend by the holders of elective mandate, since the Brazilian legislation itself favors partisan migration by establishing performance clauses for access to public funding. The reflections elaborated, however, led to the conclusion that the "windows" of the law created to exempt unfaithful representatives from penalties, contribute to intensifying the distance between voters and party entities, promoting the rise of the individual figure of the politician, which harms political representation and, consequently, the solidification of democracy.KEYWORDS: Democracy; Political Party; faithfulness.